Diseño e implementación de un sitio web para difusión de la imagen institucional, con un módulo de gestión académica para la escuela de Educación Básica Alfredo Noboa Montenegro” en el periodo 2017-2018. - Gavilanes Guaman, Luis Eduardo (2017)
At present we are in the information age, where TIC have revolutionized the way of work and diffusion, thanks to this new scenario appear new types of users known as digital natives, this has led to seek to incorporate the technology in Education, that is why the School of Basic Education "Alfredo Noboa Montenegro" seeks to implement the same that provides a series of benefits in efficiency and productivity in academic processes and dissemination, as well as increase the interest of the Children and adolescents in the aulic activities. Based on the aforementioned, the present technological proposal is presented, Design and implementation of a website for dissemination of the institutional image, with an academic management module "Virtual Platform" for the Basic Education School "Alfredo Noboa Montenegro" in the period 2017-2018, the same that arose after access to the educational institution and find a number of problems that led to the generation of this proposal. In the course of the research, information about the subject was sought in order to present a solid state of art and to substantiate the research. In the same way, a survey was conducted on the need for an institutional web site as well as a virtual platform to improve the academic processes within the educational institution, and to ratify the need Of this technological proposal. Finally, as a technological proposal, to design and implement the institutional website and virtual platform within a domain contracted for the educational institution, the same that will be used by teachers, administrators, students and parents, to disseminate and inform the services that Can offer the Institution. Also taking advantage of the facilities of the website, an Academic Management Module "Virtual platform" has been associated, the same one that will serve to support in the process of teaching learning and student accompaniment in the educational activity.